Globale Finanzinnovationen, privates Computergeid und sozialisierte Schulden - Altvater, Elmar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1996)
The aiticle does not deal with the security problems or the practicability of electronic money but with the economic problems it raises.They are analysed at first by the example of »pre-paid«-cards (off-line-money), especially regarding debtors, capital owners and the central bank’s control possibilities. Secondly, the problems are seen in the broader framework of the globalisation of financial relations and in the context of thc formation of a »derivative capitalism« and as an expression of a »privatization« of money. The conclusion is that neither derivates nor electronic money can avoid a real consolidation of value. This shows the limits of thc »viitualisation« of (electronic) money.